Navigating the Boundaries of Human Identity and Artificial Intelligence in Contemporary Literature - Shaaban Sulaiman Sadeeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study delves into the exploration of human identity and artificial intelligence (AI) in contemporary literature, with a focus on three prominent novels: Ready Player One, The Circle and Machinehood. By employing posthumanism and cyborg anthropology as theoretical frameworks, this study uncovers new insights into the increasingly blurred boundaries between biological and artificial intelligence. It investigates how these novels challenge traditional notions of human identity and consciousness while raising questions regarding the potential consequences of AI’s integration into human lives. Furthermore, this study examines the ethical implications of AI’s growing influence on privacy, autonomy, and the potential for AI-driven inequality. By addressing these themes and existential concerns, the study aims to contribute to the ongoing debate on AI’s role in society and inform future policies and guidelines for its development and integration, ultimately ensuring the preservation of human values and well-being in a rapidly evolving technological landscape